2023
DOI: 10.3389/fpls.2023.1266796
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the major gene BhHLS1 controlling seed size in wax gourd (Benincasa hispida)

Wenrui Yang,
Peng Wang,
Ting Liu
et al.

Abstract: Introduction/BackgroundThe seed size of wax gourds is an important agronomic trait; however, the associated genes have not yet been reported.MethodsIn this study, we used a high-density genetic map constructed based on F8 recombinant inbred line populations derived from a cross between MY-1 (large seed) and GX-71 (small seed) strains to detect quantitative trait locis (QTLs) for seed-size-related traits in wax gourd over a two-year period.ResultsTwo stable QTLs (qSL10 and qSW10) for seed length (SL) and seed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…Finally, the seed size gene was localized within the 48.8 Kb range and contained only one gene (Bch10G006400) (Figure 4b), which encodes a family of Nacetyltransferase proteins. It is speculated that this gene is an important candidate for determining the seed size of chieh-qua, which was consistent with the findings of previous studies of the wax gourd seed size gene [22].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Finally, the seed size gene was localized within the 48.8 Kb range and contained only one gene (Bch10G006400) (Figure 4b), which encodes a family of Nacetyltransferase proteins. It is speculated that this gene is an important candidate for determining the seed size of chieh-qua, which was consistent with the findings of previous studies of the wax gourd seed size gene [22].…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that the seed phenotype of the F 1 population was similar to that of the large-seed parent P 1 (Table 1 and Figure 1a), and the seeds of the F 2 population exhibited a bimodal distribution (Figure 1b-d). These findings are consistent with the results for the seed size of wax gourd [22]. However, some researchers believe that seed size is a quality trait, which may be caused by differences in the materials, planting methods, or statistical methods used.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations